The moon book - Gibbons, Gail. (New York : Holiday House, 1997)
Identifies the moon as our only natural satellite, describes its movement and phases, and discusses how we have observed and explored it over the years.
Elem. School Library Collection
School Library Journal
Wilson's Children
4.8
K-3
K-3
Keywords: Moon -- Juvenile literature; Moon; Moon